Higher prevalence of oral human papillomavirus infection in HIV-positive than HIV-negative Thai men and women. Issue 6 (December 2015) - Vacharotayangul, Piamkamon; Rungsiyanont, Sorasun; Lam-ubol, Aroonwan; Pankam, Tippawan; Rodbamrung, Piyanee; Naorungroj, Supawadee; Phanuphak, Nittaya
Highlights: We investigated the prevalence of oral HPV infection in HIV positive and negative Thai men and women using oral rinses with mouthwash collected at the time of examination. The prevalence of oral HPV infection was higher in HIV-positive than in HIV-negative subjects. Among HIV positive subjects, MSM had higher chance of having HPV infection than females. The high-risk HPV 16 was most the prevalent HPV in the oral cavity in our study population. Abstract: Objective: This study was designed to investigate the prevalence of oral human papillomavirus (HPV) infection among HIV-positive and HIV-negative Thai men and women. Methods: Participants including men who have sex with men (MSM) and heterosexual women were enrolled at the Thai Red Cross Anonymous Clinic in Bangkok. History taking and oral examination were performed by three independent dentists after calibration. HPV infection was evaluated from oral rinse with mouthwash collected at the time of examination. HPV typing was performed by PCR and nucleic acid hybridization to detect thirty-seven HPV DNA genotypes using Linear Array ® HPV Genotyping Test (Roche Molecular System, Inc.). Results: 244 subjects were enrolled in the study, consisted of 187 HIV-positive (51.9% women and 48.1% MSM) and 57 HIV-negative (21.0% women and 79.0% MSM) Thai subjects. The prevalence of oral HPV infection was 17.2% in HIV-positive subjects whereas only 5.3% of HIV-negative cases had HPV detected in their oral rinses ( p  = 0.0346). Among HIV positive subjects, MSM had higher chance of having HPV infection than females (25% vs. 9.4%, p  = 0.0074). Conclusions: HIV-positive Thai MSM and women had higher prevalence of oral HPV infection than those without HIV.